INTEGRATION OF NEW STUDENT ADMISSION SYSTEM WITH ACADEMIC SYSTEM (SIAK) AND UKT PAYMENT GATEWAY THROUGH APPLICATION PROGRAMMING INTERFACE (API) WITH AGILE SCRUM METHOD - Prihandani, Kamal; Solehudin, Arip; Padilah, Tesa Nur; Maulana, Iqbal (Informatics Engineering, Faculty of Engineering and Computer Science, Universitas Buana Perjuangan Karawang, 2026)
The new student admission (PMB) process at Universitas is a crucial activity that takes place every academic year. However, the registration mechanism for prospective students still relies on manual processes, where applicant data recording is performed using printed forms and the management of Single Tuition Fee (UKT) payments is not directly connected to the Academic Information System (SIAK) or banking institutions. This condition results in operational inefficiency and potential data inconsistency. This study aims to design and develop a website-based PMB UNIVERSITY application connected to SIAK for managing prospective student data and integrated with the banking system for UKT payments through an Application Programming Interface (API), adopting the Agile Scrum development method. The application was built using the Laravel framework version 10 with the PHP programming language. The development process includes requirements identification through interviews with stakeholders, product backlog preparation, system design using UML, implementation through sprints, and validation using black box testing (alpha testing) and beta testing. The alpha validation results show that all functionalities operate according to specifications, including prospective student registration, data verification through the SIAK API, and automatic UKT payment confirmation through the Bank API. The resulting application has been proven to improve the efficiency and accuracy of the new student admission process at UNIVERSITY.